2016
DOI: 10.7150/jca.16178
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer and Sensibilisation Effect of Triptolide on Human Epithelial Ovarian Cancer

Abstract: Introduction: Advanced ovarian cancer is the main cause of ovarian cancer deaths, and it is important to seek safe and effective phytochemicals to suppress cancer or lower the chemotherapy resistance of ovarian cancer.Methods: This study evaluated the effect of Triptolide (TPL) on the proliferation, cycle distribution, apoptosis, and ultra-structure of COC1/DDP cells in vitro, as well as the anti-cancer effect and sensibilisation effect of TPL in vivo.Results: The results indicated that TPL could significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…TPL, a pure compound extract from the Chinese traditional medicine T. wilfordii, has significant cytotoxic effects on ovarian cancer (Hu et al, 2016). However, the mechanisms of TPL on ovarian cancer and its target genes have not been studied (Westfall, Nilsson & Skinner, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPL, a pure compound extract from the Chinese traditional medicine T. wilfordii, has significant cytotoxic effects on ovarian cancer (Hu et al, 2016). However, the mechanisms of TPL on ovarian cancer and its target genes have not been studied (Westfall, Nilsson & Skinner, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis that TPL covalently modifies proteins via epoxide ring-opening reactions has been proved that how TPL stimulates apoptosis of cancer cells (Hu et al, 2016). Even though the target proteins are undefined, it is evident that TPL has some kind of explained effects on the anticancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural compounds such as flavones, flavonoids, and antioxidants have exhibited toxicity against ovarian cancer cells . It has been reported that triptolide, a diterpene triepoxide, exerts growth‐suppressive effects on human epithelial ovarian cancer cells . Curcumin, a polyphenolic compound found in turmeric, can trigger apoptotic death in ovarian cancer cells by disrupting calcium homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that the mechanism of tumor occurrence, development, invasion, metastasis and resistance is complex (4)(5)(6)(7)(8)(9). As one of the most well-known natural products, triptolide (TPL) had been used as an anti-inflammatory agent for rheumatoid arthritis for a long time in China, and was also recognized as a potential medicine for various types of cancers (10)(11)(12)(13)(14)(15)(16) although some researchers showed its potential toxicity on animal liver, kidney, testes, ovary and heart (17).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most well-known natural products, triptolide (TPL) had been used as an anti-inflammatory agent for rheumatoid arthritis for a long time in China, and was also recognized as a potential medicine for various types of cancers (10)(11)(12)(13)(14)(15)(16) although some researchers showed its potential toxicity on animal liver, kidney, testes, ovary and heart (17). Recent studies indicated that TPL induced cell apoptosis by inhibiting nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) in a p53-independent pathway, producing reactive oxygen species (ROS) and inactivating the PI3K/Akt signal pathway (9,16,(18)(19)(20)(21). In previous studies, our group proved that the TPL effectively inhibited cell growth, proliferation, metabolism, survival and cancer genesis by regulating the PI3K/Akt pathway (22).…”
Section: Introductionmentioning
confidence: 99%